A comparative study on the gas‐phase and liquid‐phase thermal isomerization reaction of α‐pinene. (30th August 2012) - He, Jindong; Gong, Yan; Zhao, Wentao; Tang, Xiangyang; Qi, Xin
<x xml:space="preserve">Abstract</x> In this paper, a method of preparation of ocimene is investigated, which is obtained from isomerization reaction of α‐pinene. Two kinds of experimental apparatus are established for the investigation of the thermal isomerization reaction of α‐pinene. The behavior of thermal isomerization reaction of α‐pinene is respectively discussed in the gas phase and in the liquid phase. Under gas phase conditions, the conversion of α‐pinene is 80% and the selectivity of ocimene is 30%–33%. Under liquid phase conditions, the conversion of α‐pinene is 60% and the selectivity of ocimene is 50%–54%. According to the kinetic‐molecular theory of ideal gases, two kinds of reaction models are proposed to visualize the reaction process. In addition, the mechanism and kinetics of thermal isomerization reaction of α‐pinene are respectively discussed. The conclusion is that the gas phase reaction temperature is calculated to be 390–450 °C and the liquid phase reaction temperature is calculated to be 450–550 °C. From a bond dissociation energy point of view, results support the hypothesis that the reaction involves biradical intermediates. Copyright © 2012 John Wiley & Sons, Ltd.